Current Therapeutic Strategies and Prospects for EGFR Mutation-Positive Lung Cancer Based on the Mechanisms Underlying Drug Resistance - Yukari Tsubata (MDPI AG, 2021)
The discovery of activating mutations in the epidermal growth factor receptor (EGFR) gene and the development of EGFR tyrosine kinase inhibitors (TKIs) have led to a paradigm shift in the treatment of non-small cell lung cancer (NSCLC). EGFR mutation-positive NSCLC is common in East Asia, and approximately 50% of adenocarcinomas harbor EGFR mutations. Undoubtedly, EGFR-TKIs, with their promising efficacy, are the mainstay of primary therapy. However, even if tumor shrinkage is achieved, most patients become resistant to EGFR-TKIs and relapse; hence, EGFR-TKIs do not achieve a radical cure. The problem of the development of resistance to targeted drugs has been a persistent challenge. After the role of EGFR T790M mutation in acquired drug resistance was reported, osimertinib, a third-generation irreversible EGFR-TKI, was designed to overcome the resistance conferred by T790M mutation. In addition, some studies have reported the mechanism of drug resistance caused by mutations other than the T790M mutation and strategies to overcome them. Elucidating the mechanism underlying drug resistance development and combining therapeutic approaches are expected to further improve NSCLC prognosis.